(untitled) (Global Journal of Science Frontier Research, 2018)
The collection of the Royal Museums of Fine Arts (MFA) of Brussels, Belgium covers a period extending from the 15 th to the 21 st centuries. It provides overview of western arts with remarkable ensembles of works of artists from Belgium. In the museum there a collection of paintings, sculptures, drawings and prints, it also includes, in particular through donations or deposits, items of decorative arts and furniture along with a small number of non-European works. The online catalogue currently contains over 10,000 of the most representative works of the collection. To assess the air quality inside and outside the museums the sampling campaign over a period of April 13, 2015-May 11, 2015 was performed. The gas monitoring of nitrogen dioxide (NO 2 ), sulphur dioxide (SO 2 ) and ozone (O 3 ) was carried out outside the building, in galleries and in showcases by means of using diffusive samplers. The concentrations of gaseous pollutants (NO 2 , SO 2 and O 3 ) were lower inside the museums than the outside with some of them at undetectable levels inside; in addition, the levels of these gases inside the two museums were lower and below the recommended level when compared to that of other museums (in other countries). The air conditioning system inside the museums play a great role in determines the concentrations of the pollutants.